324 A progress report for the Efficient Dairy Genome Project. (7th December 2018) - Miglior, F; Baes, C; Cánovas, A; Coffey, M; Connor, E; De Pauw, M; Goddard, E; Hailu, G; Lassen, J; Malchiodi, F; Osborne, V; Pryce, J; et al.
Abstract: The Efficient Dairy Genome Project is an international research initiative led by Canada that brings together research and industry experts and is focused on developing genomic selection tools for improving feed efficiency (FE) and decreasing methane emissions (ME) in dairy cattle. Genotypes and phenotypic data for FE, ME, and milk MIR spectral data from research herds in six countries are being collated in a secure project database for the continuous data exchange among country members. Consolidated data will be used to implement genomic evaluations for the novel traits using a combined reference population. As the 4-year project enters its final year, results in various areas are accumulating: structural variants, economic weights and selection index, consumer and producer level social studies. The project generated whole-genome sequences for 32 Holstein bulls which was combined with existing sequence data on another 451 Holstein animals from previous projects. This information has been used to find structural variants in the genome that may be contributing to or affecting these traits. Such variants will help us understand the underlying biology of these traits and/or serve as genetic markers to select desired animals.